Safety in the handling and operation of pikes - De la Cruz Carrasco, Estanislao (2000)
The most important activity in a mining operation is the extraction of the mineral (cleaning), which can be carried out by movement horizontally (locomotive, scoop, tippers), vertically (hoisting), by inclines, ramps and zig zag. To extract the underground mine ore in deposits that do not have a chamfer, it will be necessary to build a pike, which will vary in length and the capacity of the extraction tonnage. In this work, the main elements of the lifting system are treated, such as the drum, cables, pulley, cage and castles or towers. Then the management and operation of doormen and doorbells, to finally deal with the maintenance and security of the different elements of the lifting system.